Artificial Intelligence and the Future of Learning: Personalization for Equity and Engagement - Zhao Feng; I Gde Wawan Sudatha; I Komang Sudarma (Universitas Pendidikan Ganesha, 2025)
The increasing adoption of artificial intelligence (AI)-driven personalized learning technologies has reshaped educational practices toward more adaptive and learner-centered approaches. This study aims to analyze the integration and effectiveness of AI-based personalized learning within contemporary educational frameworks. Anchored in constructivist and cognitive theories, the study explores how intelligent tutoring systems, adaptive learning platforms, and natural language processing enabled feedback contribute to shifting the paradigm from teacher-centered to learner-centered learning. A mixed-method design was employed, involving interviews with educators and students, questionnaires, learning data analysis, and case studies across diverse educational contexts. Data were examined using statistical analysis, content analysis, and computational modeling to identify personalized learning pathways and evaluate their outcomes. Findings indicate that AI-driven personalization enhances student engagement, learning motivation, and academic achievement, while also supporting inclusive practices by reducing disparities in learning progress. Moreover, the results highlight the importance of algorithmic transparency and ethical considerations to ensure fairness in AI-supported education. The study concludes that rational and ethical use of AI technologies has significant potential to improve learning outcomes and equity in education. These findings imply the necessity of continuous research on algorithmic decision-making, pedagogy, and the ethical design of AI in education, providing valuable insights for the future development of personalized learning technologies.